UPAYA MENINGKATKAN KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN TEMATIK MODEL INTEGRATED - Ghina Sakina Muslimawati; Ida Ermiana; Helda Apriani; Lilis Rizkiya Amanda (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This research examines the implementation of Indonesian language learning in the 6th grade at SDN 30 Mataram, focusing on students' listening skills. In the context of integrated learning that combines Indonesian language and Social Sciences (IPS), students engage in activities that enhance language skills through the text "Sang Saka Merah Putih." Although this learning aims to introduce historical concepts and improve language skills, observations indicate that students' listening skills are still low. One student experienced difficulties in listening to the teacher's instructions, resulting in errors in the assigned tasks. This research emphasizes the importance of developing listening skills to support academic success and effective communication.